Continuous improvement in cotton processing: a case study - Amorim, Rian Moura Café; Silva, Keren Karolyne Nóbrega; Silva, Yuri Laio Teixeira Veras (Brazilian Journal of Production Engineering, 2025)
This study aims to analyze the production process of a cotton processing company, applying quality tools and statistical methods as a basis for continuous process improvement. The research is characterized as applied and experimental, with a quantitative approach, conducted in a real industrial environment. Critical process variables were evaluated, such as temperature, cotton humidity at different stages, feed rate, and equipment rotations, comparing scenarios with incorrect and correct parameters. The data were subjected to statistical analysis and instrumental verification in the laboratory, making it possible to identify the main causes of variation in operational performance. The results showed high variability in bale weight, with 77.6% non-conformity in relation to the specified limits, with 41% below and 36.6% above the standard weight. The main causes identified are related to operational failures, environmental variations, and lack of standardization between shifts. The application of quality tools allowed the identification and prioritization of the causes with the greatest impact, directing corrective actions aimed at standardizing humidification and pressing, improving communication between operators, and preventive maintenance of equipment. The study highlights the scientific relevance of integrating quality management and industrial statistics as support instruments for decision-making and continuous process improvement in agribusiness.
Keywords: Agribusiness; Quality Management; Statistical Quality Control; Cotton